The Escitalopram versus Electric Current Therapy for Treating Depression Clinical Study (ELECT-TDCS): rationale and study design of a non-inferiority, triple-arm, placebo-controlled clinical trial - Brunoni, André Russowsky (2015)
CONTEXT AND OBJECTIVE: Major depressive disorder (MDD) is a common psychiatric condition, mostly treated with antidepressant drugs, which are limited due to refractoriness and adverse effects. We describe the study ratio-nale and design of ELECT-TDCS (Escitalopram versus Electric Current Therapy for Treating Depression Clinical Study), which is investigating a non-pharmacological treatment known as transcranial direct current stimulation (tDCS). DESIGN AND SETTING: Phase-III, randomized, non-inferiority, triple-arm, placebo-controlled study, ongoing in São Paulo, Brazil. METHODS: ELECT-TDCS compares the efficacy of active tDCS/placebo pill, sham tDCS/escitalopram 20 mg/day and sham tDCS/placebo pill, for ten weeks, randomizing 240 patients in a 3:3:2 ratio, respectively. Our primary aim is to show that tDCS is not inferior to escitalopram with a non-inferiority margin of at least 50% of the es-citalopram effect, in relation to placebo. As secondary aims, we investigate several biomarkers such as genetic polymorphisms, neurotrophin serum markers, motor cortical excitability, heart rate variability and neuroimaging. RESULTS: Proving that tDCS is similarly effective to antidepressants would have a tremendous impact on clinical psychiatry, since tDCS is virtually devoid of adverse effects. Its ease of use, portability and low price are further compelling characteristics for its use in primary and secondary healthcare. Multimodal investigation of biomark-ers will also contribute towards understanding the antidepressant mechanisms of action of tDCS. CONCLUSION: Our results have the potential to introduce a novel technique to the therapeutic arsenal of treat-ments for depression. CLINICAL TRIAL REGISTRATION: ClinicalTrials.Gov NCT01894815.